An Empirical Approach to Investigate Environmental Effects on Acoustic Signal Speed in Oceanic Layers - Munim Salehin, Khondoker; Khan, Md. Khalid Mahbub; Rahman, Anisur (Archives of Acoustics, 2026)
This paper investigates and demonstrates the effects of three significant environmental contributors: temperature, depth and salinity impact on the acoustic signal propagation across distinctive ocean layers: mixed, thermocline, and deep layers. In the field of underwater wireless sensor networks (UWSN), exact and precise determination of coordinates for sensor localization is very crucial for data validation. Temperature dominates the upper layers; depth becomes the prime factor for the deeper domain with minimal thermal variations. Salinity while having a diminished effect, facilitates minor changes in propagation and deviation of acoustic signal speed. In our work we have analyzed these interdependencies by using different empirical models (e.g., Mckenzie, Medwin) customized to each layer, accounting to their incomparable environmental parameters. In mixed layers, changes in sound speed are mainly caused by thermal factors, where depth is of minimal importance, and the influence of salinity is insignificant, but with increasing depth, the temperature begins to decrease, and depth (pressure) begins to become important, and changes in salinity and temperature become almost equivalent. By evaluating ocean layer specified empirical formulas, we have calculated the average speed of sound and measure the corresponding contribution of all parameters. Our work has provided a substructure which helps to optimize the identification or localization of UWSN nodes. The results of this work underscored the essential to have an adaptive sound speed modeling in order to achieve enhanced and precise acoustic signal communication systems.